ALIRAN ADDINI AL-AQLANI (ALIRAN RELIGIUS RASIONAL) DALAM FILSAFAT PENDIDIKAN ISLAM - Asmara Hayati; Burhanudin Khairi; Dwi Suci Sisca Sari; Jamal Fakhri; Ikhsan Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic educational philosophy plays an important role in responding to contemporary educational challenges while maintaining spiritual and moral foundations. One of the significant approaches within this field is the Addini Al-Aqlani (religious-rational) school of thought, which emphasizes the harmonious integration of revelation (ad-dīn) and reason (‘aql). This article aims to examine the concept, historical background, major figures, and educational implications of the Addini Al-Aqlani school within Islamic educational philosophy. The study employs a library research method by analyzing classical and contemporary literature relevant to religious-rational perspectives in Islamic education. The findings indicate that the Addini Al-Aqlani school emerged as a response to two extreme tendencies in Islamic educational thought: rigid textualism that marginalizes reason and excessive rationalism that neglects revelation. Prominent figures such as Ikhwan al-Shafa, al-Farabi, Ibn Sina, and Ibn Miskawaih argue that reason and revelation are complementary sources of knowledge in achieving human perfection (insān kāmil). This school has significant implications for Islamic education, particularly in formulating educational objectives that balance intellectual, moral, and spiritual development, designing integrative curricula that combine revealed and rational sciences, and applying dialogical, reflective, and rational-spiritual teaching methods. Therefore, the Addini Al-Aqlani approach remains relevant as an integrative paradigm for developing Islamic education that is holistic, contextual, and value-oriented in the modern era.